Effects of Parental Monitoring and Communication on the Prevention of Sexual Risk Behavior in Adolescents: Meta-Analysis - Ayu, Elsa Jumasni; Demartoto, Argyo; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Risky sexual deviations in adolescents are habits that include having sex at an early age, using condoms that are inconsistent, having more than one sexual partner or being a commercial sex worker. Communication between parents and children plays an important role in fostering the relationship between the two and parents who are less able to communicate with their children will cause relationship conflict so that it can have an impact on adolescent sexual behavior. This study aims to estimate the influence of parental monitoring and parental communication on sexual risk behavior in adolescents based on the results of primary research. Subjects and Method: This was a review of meta-analytic studies and this article was obtained from databases namely PubMed, Google Scholar, Elsevier, Spinger Link and Science Direct. The articles used in this study are articles published from 2012-2022. The article search was carried out by considering the eligibility criteria defined using the PICO model, namely P: Adolescents, I: Parental monitoring and parental communication C: No parental monitoring and no parental communication O: Sexual risky behavior. The articles included in this research are full text articles with a cross-sectional study design. This article was analyzed using the Review Manager 5.3 application. Results: A total of 17 cross-sectional studies from 5 Americas, 1 Europe, 2 Asia and 9 Africa with a sample size of 13,404. The results of the meta-analysis showed that adolescents with parental monitoring reduced risky sexual behavior 0.84 times compared to those without parental monitoring, but the effect was not statistically significant (aOR=0.84; 95% CI=0.61-1.17; p=0.300), adolescents without parental communication has the possibility of having risky sexual behavior 1.26 times compared to adolescents who communicate with parents (aOR=1.26; 95% CI 0.81-1.95; p= 0.310) which is not statistically significant. The results of research on parental monitoring showed that there was high heterogeneity (I2=74%; p=0.001) and parental communication (I2=90%; p<0.001), so that the average effect estimation calculation on the forest plot used the random effect model. Conclusion: Parental monitoring and parental communication have no effect on sexual risk behavior in adolescents. Keywords: parental monitoring, parental communication, sexual risk behavior, youth.